Effect of dietary spirulina platensis on the fatty acid composition in flesh and ovary of walking catfish (Clarias macrocephalus) - Thaweedet Chainapong (2018)
© 2018, Chiang Mai University. All rights reserved. Spirulina platensis Geitler is widely used in aquaculture as a protein and carotenoid supplement to aquafeed. Four-month-old female walking catfish (Clarias macrocephalus) were fed with dry-pellet diets containing 0%, 5% and 10% S. platensis, during the 4-month experiment. The results showed that the feed conversion ratio (FCR) of the fish fed with 10% S. platensis supplemented diet was lower than that of control treatments (p<0.05). The main fatty acids found in the fish’s flesh and ovary were palmitic acid (C16:0), stearic acid (C18:0), oleic acid (C18:1n-9) and linoleic acid (C18:2n-6). Increasing dietary levels of S. platensis caused the increase of n-6 PUFAs (C18:2n-6, C18:3n-6, C20:3n-6 and C20:4n-6) in fish flesh. Gamma linolenic acid (C18:3n-6 or GLA) was detected as 0.34 and 0.38% of total fatty acids found in the flesh of the fish fed with 5% and 10% S. platensis supplemented diets, respectively. GLA was found at only 0.1% in the ovary of the fish from all treatments. The results indicated that an increase in the S. platensislevel in feed did not have a negative effect on growth performance and S. platensis can be used as an alternative protein source for fish meal in catfish farming. However, an increase in the level of S. platensis supplemented in fish diets was accompanied by a decrease in levels of PUFAs in fish flesh and can affect the flesh quality.